1999
DOI: 10.1071/mf98167
|View full text |Cite
|
Sign up to set email alerts
|

Length at maturity of the greeneye spurdog shark, Squalus mitsukurii (Elasmobranchii : Squalidae), from the SW Atlantic, with comparisons with other regions

Abstract: Size at maturity is analysed for Squalus mitsukurii from the SW Atlantic. Males mature between 51 and 55 cm total length and females between 52 and 60 cm total length. Hence, S. mitsukurii appears to be intermediate in size at maturity among the SW Atlantic squalid sharks. This analysis adds evidence of the plasticity of S. mitsukurii in size at maturity. The length–weight relationship did not differ between sexes in the SW Atlantic population, whereas it differed in one population from the NW Pacific. Interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 7 publications
3
48
0
1
Order By: Relevance
“…These differences may be attributable to differences in the methods for assessing maturity and/or in sample size used in each study. Another possible explanation, taking into account that C. callorynchus has a widely distribution off southern South America, is that perhaps there are multiple discrete populations of this species with latitudinal variation in size at maturity, as was suggested for several chondrichthyan species around the world (Templeman, 1987;Parsons, 1993;Lucifora et al, 1999;Chiaramonte, Petovello, 2000;Mabragaña, Cousseau, 2004;Colonello et al, 2007;Ebert et al, 2008;Barnett et al, 2009). In turn, the PCL 50 estimated in the study area was lower than those values found in northern Patagonian waters, which may be associated with the fact that coastal waters of south-eastern Buenos Aires Province support the highest pressure on chondrichthyans in Argentina (Massa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be attributable to differences in the methods for assessing maturity and/or in sample size used in each study. Another possible explanation, taking into account that C. callorynchus has a widely distribution off southern South America, is that perhaps there are multiple discrete populations of this species with latitudinal variation in size at maturity, as was suggested for several chondrichthyan species around the world (Templeman, 1987;Parsons, 1993;Lucifora et al, 1999;Chiaramonte, Petovello, 2000;Mabragaña, Cousseau, 2004;Colonello et al, 2007;Ebert et al, 2008;Barnett et al, 2009). In turn, the PCL 50 estimated in the study area was lower than those values found in northern Patagonian waters, which may be associated with the fact that coastal waters of south-eastern Buenos Aires Province support the highest pressure on chondrichthyans in Argentina (Massa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The size at sexual maturity is of special interest in fisheries management, which is widely used as an indicator for minimum permissible capture size (Lucifora et al, 1999). Available information on size at sexual maturity of fishes can be obtained from the plots of percentage occurrence of mature females against length class using logistic equation (King, 2007), though few studies (Gab-Alla et al, 1990;Hossain et al, 2012a) have reported low accuracy of estimating size at sexual maturity using logistic equation.…”
Section: Discussionmentioning
confidence: 99%
“…Tormosoval (1983) density, food, and water temperature might influence the growth of fish and further affect their size at first maturity. As the parameter is useful for endangered species management, this information can be used to suggest mesh sizes for conservation measures to be adopted by fishery administrators to avoid overfishing (Lucifora et al, 1999). The size and number of eggs and larvae produced by individual fish are determined by the predictability of survival and trade-offs in energy allocation to reproduction, growth, behavior and maintenance (Smith and Fretwell, 1974;Roff, 2000).…”
Section: Discussionmentioning
confidence: 99%